The Role of Quality Management in Customer Satisfaction in Fashion E-Commerce: A Literature Review - Vera siwi Astuti; Hanifah Nur Aisyah; Rusnandari Retno Cahyani (Management Study Program, Universitas Kristen Indonesia Paulus, 2026)
This study aims to analyze the role of quality management in improving customer satisfaction in fashion e-commerce. The rapid growth of e-commerce in Indonesia has intensified competition, making product and service quality key factors in maintaining customer satisfaction. This study employs a literature review method by examining relevant journals, books, and credible sources published within the last 5–7 years. The findings indicate that quality management has a significant effect on customer satisfaction, reflected in product conformity with descriptions, ease of platform use, responsiveness of services, and delivery accuracy. In addition, product quality and service quality are interrelated in shaping the overall customer experience. The implementation of effective quality management not only enhances customer satisfaction but also fosters customer loyalty and business sustainability. Therefore, quality management is a crucial strategy for fashion e-commerce businesses in facing increasingly competitive market conditions.